(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The use of digital photography medium is dominantly used in the process of investigating criminal cases. Digital photography used in the investigation process is also known as crime scene photography, where photographic images are produced to collect evidence, documenting the scene, and subsequently, be used as a reference for criminal case investigation and prosecution process. Using systematic literature review (SLR), this study identifies the current practice of digital use of photography in the process of investigating criminal cases. Searches via electronic databases of indexed journals, namely, Scopus, Science Direct, Web of Science and Springer were conducted. Data is limited to these journals was produced within the years 2017 until 2021 as the latest research information. The findings consist of 28 papers that had met the criteria by which this study touched on digital photography technology such as DSLR Camera, Drone Photography, and CCTV.